Application of survival analysis to model proliferation likelihood of Escherichia coli biofilm following laser-induced hyperthermia treatment - Burden, Bradley; Rodriguez-Alvarez, Juan Sebastian; Levi, Nicole; Gayzik, F. Scott (Frontiers in Bioengineering and Biotechnology, 2023)
Eighty percent of bacterial infections associated with living tissue and medical devices are linked to drug-resistant biofilms, leading to lengthy and costly recoveries. Laser-induced hyperthermia can to disrupt cell proliferation within biofilms and increase susceptibility to antibiotics. However, there can be bacterial survival differences dependent upon laser irradiation times, and prolonged time at elevated temperature can damage healthy tissue. The objective of this study was to use survival analysis to model the impact of temperature increases on reducing viable biofilm bacteria. In vitro biofilms of Escherichia coli were grown on silicone discs or silicone doped with photothermal poly(3,4-ethylenedioxythiophene) hydrate (PEDOT) nanotubes, and subjected to laser-induced hyperthermia, using a 3 W continuous wave laser at 800 nm for varying times. The number of colony forming units per milliliter (CFU/mL) and maximum temperature were measured after each trial. Survival analysis was employed to estimate bacterial cell proliferation post-treatment to provide a quantitative framework for future studies evaluating photothermal inactivation of bacterial biofilms. The results demonstrate the first application of survival analysis for predicting the likelihood of bacterial cell proliferation based on temperature.